(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Celiac disease (CD) is a chronic disease of immune-mediated damage to the small intestine resulting in variable symptoms of malabsorption. Iron deficiency anaemia (IDA) is one such frequent symptom. As these are high percentages for celiac disease in patients presenting with iron deficiency anaemia, the study’s main aim was to determine the frequency of celiac disease in children presenting with IDA. Material and Methods: It was a descriptive cross-sectional study conducted at Children’s Hospital & the Institute of Child Health, Multan, for a duration of 6 months from 16th January 2020 to 15th July 2020. A total of 132 patients were enrolled; we included patients from Ages one year to 14 years of both genders, newly diagnosed patients with iron deficiency anaemia who are not taking treatment for this, we studied age, sex, duration of anaemia, the severity of anaemia, we investigated Hb, serum ferritin, anti-tissue transglutaminase antibodies level and endoscopic biopsy done. Results: We enrolled 132 patients presenting with IDA. Among all 132 patients, CD was found in 23 (17.4%) Mean age of the patients was 7.61±4.21 years. The mean value of the duration of anaemia of the patients was 20.39±6.17 days. 60(45.45%) patients were male, and 72 (54.55%) were female. Conclusion: The frequency of CD in children with iron deficiency is found to be 17.4%. Therefore, we recommend a Multicenter study at regional and national levels to assess the disease burden and early diagnosis for appropriate and timely management of this vulnerable population.